2022
DOI: 10.1097/corr.0000000000002360
|View full text |Cite
|
Sign up to set email alerts
|

Is High-dose Radiation Therapy Associated With Early Revision Due to Aseptic Loosening in Patients With a Sarcoma of the Lower Extremities Reconstructed With a Cemented Endoprosthesis?

Abstract: Background The durability of endoprostheses after limb salvage surgery is influenced by surgical factors (resection length, implant location, and residual bone quality), implant design (modular versus custom design, rotating versus fixed hinge, coating, collars, and the use of cross pins), and host factors (patient's immune status, activity One of the authors (NMB) certifies receipt of personal payments or benefits, during the study period, in an amount of USD 100,001 to USD 1,000,000 from Daiichi Sankyo Inc; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 40 publications
(89 reference statements)
0
10
0
Order By: Relevance
“…In this large 40-year endoprosthesis database study from Los Angeles (California, USA) , the authors analyzed patients who received radiation to the extremity to investigate the association between preoperative or postoperative radiation therapy and endoprosthesis survival. 1 Overall, 207 patients met inclusion criteria and were eligible for analysis. The mean implant survival time for patients who did not receive radiation was 18.3 years, while the mean implant survival times for patients who received 3,000 cGy and > 3,000 cGy of radiation were 19.1 years and 13.8 years, respectively.…”
Section: Is High-dose Radiation Therapy Associated With Early Revisio...mentioning
confidence: 99%
“…In this large 40-year endoprosthesis database study from Los Angeles (California, USA) , the authors analyzed patients who received radiation to the extremity to investigate the association between preoperative or postoperative radiation therapy and endoprosthesis survival. 1 Overall, 207 patients met inclusion criteria and were eligible for analysis. The mean implant survival time for patients who did not receive radiation was 18.3 years, while the mean implant survival times for patients who received 3,000 cGy and > 3,000 cGy of radiation were 19.1 years and 13.8 years, respectively.…”
Section: Is High-dose Radiation Therapy Associated With Early Revisio...mentioning
confidence: 99%
“…In this issue of Clinical Orthopaedics and Related Research ® , Arnold et al [2] analyzed a nearly 40-year single-institution cohort of 207 patients treated with cemented endoprostheses and chemotherapy with or without radiation therapy for lower extremity malignancies. They reported decreased implant survivorship for patients treated with high-dose (> 3000 cGy) radiation and decreased 5-year survival regarding amputation or revision for aseptic loosening compared with endoprostheses that were not treated with therapeutic radiation.…”
Section: Where Are We Now?mentioning
confidence: 99%
“…Nonetheless, based on the findings in this study [2], surgeons might consider, particularly for patients with higher-dose radiation, additional means of supplemental stabilization or fixation (whether via side plates, cross pins, or longer stems, anatomy permitting), more-detailed patient counseling about the long-term risks of radiation and implant loosening, or closer continued surveillance.…”
Section: Where Are We Now?mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of this study showed that increased stem diameter was associated with improved outcomes, and they postulated that decreasing torsional moments around the stem may further improve cemented distal femoral replacement outcomes. Another study using the same database [1] found that high-dose radiation may be associated with higher rates of aseptic loosening in patients with primary cemented segmental implants. For this reason, they recommended closer monitoring for radiolucencies around implant stems and raised the possibility of cross-pin fixation to partially mitigate this risk.…”
mentioning
confidence: 99%